Surveillance of healthcare utilisation related to cannabis following the introduction of medical cannabis in Thailand - Bundit Sornpaisarn; Nisachol Dejkriengkraikul; Weena Thitipraserth; Waranist Lamyai; Warot Lamyai; Yot Teerawattananon; Sarnti Sornpaisarn; Thapanawong Mitsungnern; Warangkana Pongpat; Chitlada Limjindaporn; Borwon Wittayachamnankul; Pavita Laohakul; et al. (Journal of Cannabis Research, 2026)
Abstract Background Thailand introduced medical cannabis in February 2019. This study aims to monitor cannabis-related healthcare utilisation after this introduction. Methods A three-year surveillance system was established in 2021, comprising: (1) monitoring cannabis-related healthcare visits within the medical cannabis-service system and (2) assessing cannabis use outside of this system in psychiatric hospitals, youth detention centres, and emergency departments. Results During the first surveillance year (June 2021–May 2022), the Thai healthcare system rapidly expanded cannabis services, with 90.4% (95%CI: 84.4%, 96.4%) of hospitals providing medical cannabis clinics in 2022, up from just 2.8% in 2019. Nearly all providers followed clinical assessment guidelines, though about a third of them did not perform the recommended blood tests before prescribing. Of patients who received prescribed medical cannabis, 86.4% (CI: 81.4%, 91.3%) operated a vehicle within 12 h of cannabis use in the past three months. As well, 24.3% (18.5%, 30.1%) of juvenile detainees and 5.6% (4.6%, 6.5%) of the patients with psychosis admitted to psychiatric hospitals reported cannabis use in the past three months, predominantly of illegal forms like flowers (over 70%). No significant evidence of diversion of medical cannabis to these two vulnerable groups was observed during surveillance, with less than 2.5% in either group reporting using medical cannabis. The one emergency department sampled saw an average of 3.5 (1.4, 7.6) cannabis-related cases per month. Conclusions This pioneering surveillance project provides critical baseline data on cannabis-related health service utilisation in Thailand, following the introduction of medical cannabis. The findings highlight the need for ongoing, comprehensive monitoring systems to inform policy as recreational use becomes more prevalent.